Speech Acts and Politeness in Political Campaigns: An Applied Linguistics Study - Purnomo, Budi (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study examined the use of speech acts and politeness strategies in political campaign billboards from an applied linguistics perspective. It aimed to reveal how linguistic choices in political messages reflected persuasive and culturally appropriate communication during the 2025–2030 gubernatorial election in Central Java, Indonesia. A total of 200 billboard texts representing two candidate pairs were collected and analyzed using a qualitative descriptive approach. The analysis applied speech act theory to identify locutionary, illocutionary, and perlocutionary acts, as well as politeness maxims to explore social values embedded in the language use. The findings showed that directive and expressive acts were dominant, functioning to attract public sympathy and reinforce candidate credibility. Positive politeness strategies were frequently employed to maintain social harmony and align with Javanese cultural norms of respect and humility. The study contributes to applied linguistics by demonstrating how pragmatic competence operates in real-life persuasive discourse and offers pedagogical insights for teaching pragmatic awareness in political and professional communication contexts.